Pengaruh Current Ratio, Total Asset Ratio, Return on Investment, Ukuran Perusahaan (Size) dan Inflasi Terhadap Return Saham (Studi Empiris pada Perusahaan yang Tergabung dalam Jakarta Islamic Index Tahun 2007 – 2013) - Agus Budiwaluyo (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2017)
This study aimed to examine the influence of variables Current Ratio (CR), Total Asset Turnover (TATO), Return on Investment (ROI), company size (Size) and Inflation on Stock Return firms listed on the Jakarta Islamic Index (JII) 2007-2013.            The sampling technique used was purposive sampling with criteria: (a) Listed in the published list of stocks in the index calculation JII announced the Indonesia Stock Exchange in a row during the study period (b) Registered and active trading in Indonesia Stock Exchange during the period (c) The Company publishes the audited financial statements for the period 2007-2013, (d) Publish an annual report in a row during that period. Obtained a sample of 11 companies from 30 companies registered as members of the Jakarta Islamic Index are listed on the Stock Exchange. Technical analysis used is multiple linear regression and hypothesis testing using the F-test to test the effect of simultaneous and t-test to test the partial effect on stock returns with a significance level of 5%..             Simultaneous testing indicates variables Current Ratio (CR) and Total Asset Turnover (TATO), Return on Investment (ROI), company size (Size) and Inflation significant effect on Stock Return firms listed on the Jakarta Islamic Index (JII ).            Partial test results indicate that the Current Ratio (CR), Return on Investment (ROI) and Firm Size (Size) no significant effect on Stock Return, while the total asset turnover variables and inflation effect on stock returns firms listed on the Jakarta Islamic Index (JII).